KRIMINALISASI BALAP LIAR SEBAGAI PENGGUNAAN RUANG PUBLIK SECARA MELAWAN HUKUM DALAM PERSPEKTIF HUKUM PIDANA - Pascal Timothy Massie (Darma Cendika Catholic University, 2025)
Illegal racing on the highway without a permit is a form of law violation that often occurs, which not only endangers individual safety, but also disrupts public order and damages the function of public spaces. This article aims to analyze the application of criminal law to perpetrators of illegal racing and examine the role of public space in the context of unlawful use. Based on Law no. 22 of 2009 concerning Road Traffic and Transportation (LLAJ) and the Criminal Code (KUHP), illegal racing can be subject to criminal sanctions in the form of imprisonment or fines. This research found that illegal racing can be categorized as an unlawful act that disrupts public order and endangers public safety. Law enforcement against illegal racing still faces a number of obstacles, including limited resources for law enforcement officers and a lack of official racing facilities. Therefore, preventive steps are needed in the form of increasing law enforcement, providing legal racing facilities, and educating the public to prevent further violations. It is hoped that this research can contribute to the development of more effective policies in dealing with the problem of illegal racing in Indonesia.